Mesopotamia dan Mesir Kuno: Awal Peradaban Dunia - Umar, Mustofa (el Harakah: Jurnal Budaya Islam, 2009)
The existence of civilization cannot be separated from the existence of human beings. Mesopotamia and Ancient Egypt were the centers of the oldest civilization in the world. Both Mesopotamia and Ancient Egypt had typical characteristics. Mesopotamian civilization was more non-physical compared to Egypt. Sciences were emphasized more in Mesopotamia, while Egypt emphasized religious aspects. Political systems in both areas were almost the same, that is, absolutism and considered the king as god. Mesopotamia was more humanist than Egypt. The effectiveness of both civilizations was determined much by political power and economy. Keberadaan peradaban tak lepas dari keberadaan manusia. Mesopotamia dan Mesir Kuno adalah pusat peradaban tertua di dunia. Mesopotamia dan Mesir Kuno memiliki ciri khas. Peradaban Mesopotamia lebih bersifat non fisik dibandingkan dengan Mesir. Ilmu pengetahuan lebih ditekankan di Mesopotamia, sementara Mesir menekankan aspek religius. Sistem politik di kedua wilayah hampir sama, yaitu absolutisme dan menganggap raja sebagai tuhan. Mesopotamia lebih humanis daripada Mesir. Keefektifan kedua peradaban itu ditentukan oleh kekuatan politik dan ekonomi.